KARAKTERISTIK PENULISAN ARTIKEL ILMIAH PADA JURNAL NASIONAL TERAKREDITASI - Ma’arif, Tubagus Mahar; Hayadi, B. Herawan; Rukiyah, Rukiyah; Salbiah, Siti; Ningsih, Devi Sri Cahya; saputra, A Dicky wahyu (Jurnal Ilmiah Pendidikan dan Keislaman, 2026)
Writing scientific articles is the art of communicating truth through measurable logic. This study aims to map the fundamental characteristics of scientific articles in accredited national journals through an analysis of 15 recent literature sources (2024–2026). Employing a literature review method, this study explores the dimensions of rhetorical structure, linguistic quality, and the integration of AI technology in writing. The results indicate that publication success is significantly determined by the sharpness of the IMRAD pattern, the objectivity of interpersonal metafunctions in language, and strict ethical compliance. This article concludes that high-quality scientific writing is a blend of technical proficiency and the intellectual honesty of the author.